Pertimbangan Hakim dalam Pembuktian dan Perlindungan Korban Tindak Pidana Kekerasan Seksual (Studi Kasus Perkara Nomor 1650/Pid.B/2025 PN Sby) - Pricelia Anggita Togatorop; Erny Herlin Setyorini (Media Hukum Indonesia (MHI), 2026)
This article examines judicial considerations in the assessment of evidence and the fulfillment of victims' rights in a sexual violence case, using Decision Number 1650/Pid.B/2025/PN Sby as the unit of analysis. The study is motivated by the issue of how Law Number 12 of 2022 on Sexual Violence Crimes (hereinafter referred to as the Sexual Violence Crimes Law/UU TPKS) is applied by judges in evaluating the elements of consent, the perpetrator's control over the victim, and evidentiary standards within a legal paradigm that has traditionally relied on proof of physical violence. This research employs a normative juridical method using both statutory and case approaches, analyzing court decisions, legislation, and secondary legal materials through qualitative analysis. The findings indicate that the Panel of Judges applied Article 6(b) of the UU TPKS based on the principle of lex specialis derogat legi generali. The judges established their conviction by assessing the interrelationship among the items of evidence in accordance with Article 184 of the Indonesian Criminal Procedure Code (KUHAP), without treating the Visum et Repertum as the sole basis for proof. This approach is consistent with the paradigm of the UU TPKS, which places the absence of consent and the perpetrator's control over the victim at the core of the offense. Nevertheless, the judgment did not fully incorporate the victim's right to restitution and failed to adequately consider the psychological impact on the victim when determining the proportionality of the sentence. As a result, the victim-centered justice approach envisioned by the UU TPKS has not yet been fully realized.